Vico Wallari - San Genesio ricerca storica e indagini archeologiche su una comunità del medio Valdarno inferiore fra alto e pieno medioevo - Cantini, Federico; Salvestrini, Francesco (Centro di Studi sulla Civiltà del Tardo Medioevo San Miniato, 2010)
The volume collects the reports presented during the study day held in San Miniato on December 1, 2007, dedicated to the historiographical investigation and to an assessment of the long archaeological research conducted on the site of San Genesio in the lower Valdarno, a village that witnessed settlement continuity from Antiquity to the middle thirteenth century and which was definitively abandoned following a violent destruction by the inhabitants of the nearby village od San Miniato al Tedesco. From written sources we know that the locality is renown for relevant political meetings and assemblies held there between the 11th and 12th centuries; these assemblies were destined to play a significant role in the wider context of municipal Tuscany. The inhabited area was brought to light during an almost ten-year excavation campaign that has provided very important results making it a very interesting case study. The volume is a comparison between historical and archaeological methodology and aims to highlight the great utility of interdisciplinary collaboration on the analysis of especially relevant samples. At the same time, it provides a first overall picture on the history of an abandoned centre offering a rich and exceptionally documented past, proposing a point of reference for other similar investigations intended to shed light on political events, on ecclesiastical institutions and on the dynamics of population in the Medieval Italy.